Product-focused software process improvement : 18th International Conference, PROFES 2017, Innsbruck, Austria, November 29-December 1, 2017, Proceedings /: 18th International Conference, PROFES 2017, Innsbruck, Austria, November 29-December 1, 2017, Proceedings. (2017) - Unknown
No abstract available